Moisture-Dependent Physical Properties of Chia (Salvia hispanica L.) Seeds - Guiotto, Estefania Nancy (2011)
The dependence of physical properties of dark and white chia seeds on moisture content (MC) was determined in moisture ranges of 4.6% to 17.7% and 4.9% to 16.2% dry basis (d.b.), respectively. The length, width, thickness, geometric diameter, and specific surface area increased linearly from 1.91 to 2.07 mm, 1.24 to 1.34 mm, 0.81 to 0.87 mm, 1.24 to 1.34 mm, and 4.85 to 5.67 mm2 for dark seeds and from 1.92 to 2.07 mm, 1.26 to 1.32 mm, 0.81 to 0.86 mm, 1.25 to 1.33 mm, and 4.94 to 5.56 mm2 for white seeds, respectively. Seed volume, equivalent diameter, and thousand seed mass ranged from 1.09 to 1.31 mm3, 1.28 to 1.36 mm, and 1.230 to 1.352 g for dark seeds and from 1.02 to 1.25 mm3, 1.25 to 1.34 mm, and 1.170 to 1.293 g for white seeds, respectively, with the increase in MC. True density diminished from 1.115 to 1.025 g cm-3 and from 1.144 to 1.028 g cm-3 for dark and white seeds, respectively. Bulk density, porosity, and static coefficient of friction were assessed for dark seeds. Bulk density decreased from 0.713 to 0.644 g cm-3, while the porosity values varied polynomially. The static coefficient of friction on galvanized iron and aluminum increased from 0.25 to 0.34 and from 0.26 to 0.34, respectively. Results showed that seed MC affected the physical properties studied for both types of seeds.